Development of dummy molecularly imprinted based on functionalized silica nanoparticles for determination of acrylamide in processed food by matrix solid phase dispersion - Arabi, Maryam; Ghaedi, Mehrorang; Ostovan, Abbas (Food chemistry, 2016)
The MISNPs-MSPD extraction procedure. [Display omitted] •We develop a new strategy for synthesis novel dummy molecularly imprinted silica nanoparticles.•We employed propanamide as dummy template successfully.•The dummy molecularly imprinted silica nanoparticles were used as sorbent in MSPD.•Improving existing method for biscuit and bread analysis in agreement with the green chemistry.•The proposed method has the advantage of facility, simplicity and high-efficiency. A novel technique was applied for the synthesis of dummy molecularly imprinted silica nanoparticles (DMISNPs). DMISNPs were characterized by Fourier transmission infrared spectrometry, scanning electron microscopy and transmission electron microscope. The material was used as dispersant for the analysis of biscuit and bread samples using matrix solid phase dispersion (MSPD). Of advantages of such approach may be counted as the simplicity of synthesis procedure, low consumption of organic solvent, mild working temperature during the synthesis, high binding capacity and affinity. The effect of various parameters such as sample-to-dispersant ratio and eluents volume on extraction recovery was investigated and optimized by central composite design under response surface methodology. It was proven that the proposed dispersant leads to high affinity toward acrylamide even in complicated matrices. Quantification of the acrylamide was carried out by high performance liquid chromatography with UV detection (HPLC-UV).